(untitled) (International Journal of Engineering and Computer Science, 2018)
This paper presents the applications of intelligent control techniques implemented for roll angle control of aircraft system. The aircraft roll control system is designed with rate gyro and rate integrating gyro. The controllers are designed on the basis of dynamic modeling of the aircraft system for roll angle control. The modeling begins with a derivation of suitable mathematical model to describe the lateral dynamic motion of the aircraft. The roll angle of aircraft is controlled by ailerons on either side of aircraft. The simulation model for aircraft roll angle control is implemented using various controllers as cited below. A comparative assessment between PID, ANN, Fuzzy, Fuzzy-PID and ANFIS controllers based on time response specifications has been investigated and analyzed using MATLAB Simulink©.